PISA 2009 : cognitivismo e competências de leitura - Siqueira, Monique Silva Mendonça (2014)
It is not known what are the factors that lead to the unsuccess of many students concerning the reading skills. With the intent of knowing about national education based not only on national evaluations, Brazil has joined PISA (Programme for International Student Assessment) since 2000. The aforementioned exam is applied to 15-year-old students in more than 60 countries, and it indicates the average of reading and literacy skills of each state, making possible the reflection on teaching process. Through the result of that assessment, it is possible to verify that Brazilian students, especially in Sergipe, present a low reading skill when it is related to their age group. In this sense, this study has as its focus on analysing PISA´s exam of 2009 (the only area analysed here is the Reading part, therefore, Science and Mathematics will not be taken into account), by observing the converging points between the exam, the official documents and cognitive linguistics. It was analysed the results of questionnaires applied to three state schools in Aracaju, which participated of the assessment in 2009, observing the conceptions of reading adopted by some teachers, the reading activities that they developed in classroom and the common types of questions in their exams. Taking into consideration the analyses of those questionnaires as well as some questions of the exam, it was noticed that there is a divergence between what is taught during classes and what is asked in the exam. Furthermore, many teachers do not know exactly what is the reading conception adopted in the exam. Finally, it is expected with that result that reading skills of Sergipe´s students as well as policies of support to teachers are improved.